Different Monoclonal Antibodies in Myasthenia Gravis: A Bayesian Network Meta-Analysis - Song, Zhaoming; Zhang, Jie; Meng, Jiahao; Jiang, Guannan; Yan, Zeya; Yang, Yanbo; Chen, Zhouqing; You, Wanchun; Wang, Zhong; Chen, Gang (Frontiers in Pharmacology, 2022)
Background: Myasthenia gravis (MG) is a common autoimmune disease with acquired neuromuscular transmission disorders. Recently, monoclonal antibodies have been shown to successfully treat a variety of diseases. Methods: In this meta-analysis, an appropriate search strategy was used to search eligible randomized controlled trials (RCTs) on different monoclonal antibodies to treat patients with MG published up to September 2021 from the Embase, PubMed, and Cochrane Library. We assessed the average difference or odds ratio between each drug and placebo and summarized them as the average and 95% confidence interval (CI), respectively Results: In indicators of efficacy, patients receiving eculizumab (OR, -1.9; 95% CI, -3.2–-0.76) had decreases in MG-ADL scores compared to placebo. In addition, only eculizumab (OR, -3.1; 95% CI, -4.7–-1.5) and efgartigimod (OR, -1.4; 95% CI, -2.1–-0.68) showed a significant difference from placebo in the amount of reduction in QMG scores, while neither of the other two monoclonal antibodies was statistically significant. With regard to the safety of monoclonal antibody therapy, there was no significant difference in the probability of AE in subjects treated with any of the four monoclonal antibodies compared to placebo. Conclusions: Eculizumab was effective in reducing MG-ADL scores and QMG scores in myasthenia gravis. Meanwhile, eculizumab also caused fewer AE. As an emerging therapy, monoclonal antibodies are prospective in the treatment of MG. However, more researches are required to be invested in the future as the results obtained from small sample sizes are not reliable enough.